Pengaruh Faktor Internal dan Eksternal Terhadap Tingkat Kesehatan Bank - Nuryasman MN, Liliani Wijaya, (Jurnal Ekonomi, 2018)
This search has a purpose to provide emperical evidence about factors that affect health of banks. The examine factors internal on this research are CAMELS and the examine factor external on this research is Gross Domestic Product (GDP). The sample consist of 29 banks.Object of this study is the commercial banks operating in Indonesia in 2012-2015. Determination of sampling technique using purposive sampling method in which the sample is taken with certain criteria. Because the data is used are secondary datawith a quantitative approach, it is necessary to determine the accuracy of the model on some assumption of hypothesis testing using Stata tools. The result showed a partial variable NPL and IER are significant effect on the level of health. While variable CAR, NPM, ROA, LDR, and GDP insignificant effect of the health of the bank. During the period 2012-2015 there were more than 50% showed a stable bank or banks that are in the tittle of â€œFitâ€. Although they are some banks that have increased and decreased to earn the tittle of â€œunhealthyâ€ for 4 periods.